ANALISIS FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN TINGKAT DEPRESI PADA PASIEN DENGAN KEGANASAN GINEKOLOGI DI RUMAH SAKIT DR. SARDJITO YOGYAKARTA - , Selamat Widodo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The increase of screening program, the success of medicine, and the consequences of rising life survival rate already make the relations between psychosocial aspect in gynecology oncology to be something interesting. In another studies before, it is reported that patients who have 20%-25% of gynecology malignancy having depression. Objective: To know the relations between risk factors and depression, and to know what kind of risk factors that has significant effect to depression at gynecology malignancy patient at Dr. Sardjito Yogyakarta Hospital Methods: This research is done by using survey method with cross sectional framework for gynecology malignancy patient at Dr. Sardjito Hospital on December 2010 â February 2011. This analysis is using chi square test in order to know the relation between variable. Not only that, this analysis is also using regression logistic analytic in order to know the most significant factors. Result: After the analysis of risk factors is taken from 81 respondents who have depression. It is concluded that risk factors has significant effect toward depression. This result means that risk factors has together impact toward depression. The risk factors that has the most significant effect toward depression is how long the diagnosis is straighten. This result shows that every patient who have been diagnosed has cancers will eventually feeling worried and afraid Conclusion: There is significant effect between risk factors toward depression. How log the diagnosis is straighten and the age of patients are the risk factors that has the most influential toward depression.